2022
DOI: 10.1364/ao.467660
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of optic-fiber-based weak-value amplification against amplitude-type noise

Abstract: Experiments based on a free-space platform have demonstrated that the weak-value amplification (WVA) technique can provide high sensitivity and precision for optical sensing and metrology. To promote this technique for real-world applications, it is more suitable to implement WVA based on an optical-fiber platform due to the lower cost, smaller scale, and higher stability. In contrast to the free-space platform, the birefringence in optical fiber is strong enough to cause polarization cross talk, and the ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
2
0
Order By: Relevance
“…Recently, numerous works have introduced the standard weak-value amplification (SWVA) technique into a fiber optical sensor system for higher sensitivity and lower noise floor [29][30][31]. Particularly, Liu et al demonstrated an ultra-low noise phase measurement of an optic sensor based on SWVA.…”
mentioning
confidence: 99%
“…Recently, numerous works have introduced the standard weak-value amplification (SWVA) technique into a fiber optical sensor system for higher sensitivity and lower noise floor [29][30][31]. Particularly, Liu et al demonstrated an ultra-low noise phase measurement of an optic sensor based on SWVA.…”
mentioning
confidence: 99%